Z badań wykopaliskowych i inwentaryzacyjnych w Nowym Krakowie, gm. Darłowo, stan. 1 - Skrzypek, Ignacy (Folia Praehistorica Posnaniensia, 2018)
The article presents history of hitherto conducing studies at this site. It is also aimed at presentation of a short-lived excavation of the early Roman Iron Age burial mound as well as the Hallstatt settlement features, conducted in the 1991 season.